Climate change, agriculture and international migration nexus: African youth perspective - Bezu, Sosina; Demissie, Teferi Dejene; Abebaw, Degnet; Mungai, Catherine; Samuel, Seble; Radeny, Maren A.O.; Huyer, Sophia; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate change is expected to contribute to the migration of tens of millions of people in the coming decades. While some migration will be caused by sudden-onset events, such as floods, the majority will be due to the long-term impact of climate change on livelihoods. Agrarian countries are particularly vulnerable to this climate change impact as the majority of their people depend on environmental resources and vulnerable ecosystems for their livelihoods.